2021
DOI: 10.1016/j.ophtha.2020.07.060
|View full text |Cite
|
Sign up to set email alerts
|

Nonadherence or Nonpersistence to Intravitreal Injection Therapy for Neovascular Age-Related Macular Degeneration

Abstract: Topic Systematic review of risk factors for non-adherence and non-persistence to intravitreal anti-vascular endothelial growth factor (anti-VEGF) injection therapy for neovascular age-related macular degeneration (nAMD). Clinical Relevance Lack of adherence (non-adherence) or under-treatment (non-persistence) with respect to evidence from clinical trials remains a significant barrier to optimizing real-world outcomes for patients with nAMD. Contributing factors and stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
131
2
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(140 citation statements)
references
References 53 publications
5
131
2
2
Order By: Relevance
“…Since IVT injection therapy is typically prescribed on a pro re nata basis, it may not be achieving the same functional outcomes as primary clinical trials had shown. Under-prescription is influenced by similar factors to non-compliance such as socioeconomic status, transportation, and access to other resources 25 , 27 . For IVT therapy, there are no precise definitions for non-compliance, non-persistence, or non-adherence which may cause biases when assessing these rates in the literature 27 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since IVT injection therapy is typically prescribed on a pro re nata basis, it may not be achieving the same functional outcomes as primary clinical trials had shown. Under-prescription is influenced by similar factors to non-compliance such as socioeconomic status, transportation, and access to other resources 25 , 27 . For IVT therapy, there are no precise definitions for non-compliance, non-persistence, or non-adherence which may cause biases when assessing these rates in the literature 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Under-prescription is influenced by similar factors to non-compliance such as socioeconomic status, transportation, and access to other resources 25 , 27 . For IVT therapy, there are no precise definitions for non-compliance, non-persistence, or non-adherence which may cause biases when assessing these rates in the literature 27 . Thus, despite the efficacy of IVT therapeutics, poor persistence and compliance rates may continue to hinder the overall number of positive outcomes among affected patients.…”
Section: Discussionmentioning
confidence: 99%
“…Неприверженность лечению и несоблюдение режима дозирования в настоящее время рассматриваются в качестве одной из важнейших проблем, препятствующих предотвращению потери зрения при нВМД, несмотря на успех основных клинических исследований, доказывающих эффективность применения анти-VEGF терапии [26]. В некоторых публикациях указывается, что частота несо-Обзоры блюдения режима терапии и неприверженности лечению достигает 60% при сроке наблюдения 2 года.…”
Section: проблема неприверженности лечениюunclassified
“… 15 16 The nAMD literature suggests that loss to follow-up after initiating treatments is highest in the first year. 16–18 Many determinants of non-adherence/non-persistence in patients treated with intravitreal injections for nAMD are unmodifiable, such as age, visual acuity and ocular or systemic comorbidities when commencing treatment. However, other key barriers—such as distance from the hospital, 17 18 travel times and transportation implications 19 —could be addressed by improving health service delivery, with some small studies suggesting that ‘one-stop’ style services combining monitoring and injections could improve adherence.…”
Section: Introductionmentioning
confidence: 99%
“… Summary of factors that may affect acceptability of intravitreal treatments, based on the neovascular age-related macular degeneration literature. 16 58 59 …”
Section: Introductionmentioning
confidence: 99%